The Analysis Study of Intravenous Immunoglobulin for Myasthenia Gravis: Insight from A Systematic Review - Suwandhi (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Introduction: Myasthenia gravis (MG) is a chronic autoimmune disorder characterized by impaired neuromuscular transmission, leading to muscle weakness and fatigue. Intravenous immunoglobulin (IVIg) has emerged as a key therapeutic option for MG, particularly in acute exacerbations and myasthenic crises. This systematic review evaluates the efficacy, safety, and optimal use of IVIg in MG management. Methods: Following SWiM guidelines, this review synthesizes data from randomized controlled trials, cohort studies, and other high-quality evidence published between 2015 and 2025. The analysis focuses on IVIg's mechanisms of action, including neutralization of autoantibodies, inhibition of complement activation, and modulation of cytokines. Results: Studies indicate that IVIg improves clinical outcomes in 73-76% of patients, with a favorable safety profile compared to plasma exchange (PLEX). However, questions remain regarding its role in chronic maintenance therapy, corticosteroid-sparing effects, and long-term outcomes. Emerging therapies, such as subcutaneous immunoglobulin (SCIG), FcRn inhibitors (e.g., efgartigimod), and complement inhibitors (e.g., zilucoplan), offer promising alternatives with potential advantages in convenience and specificity. Conclusion: While IVIg remains a cornerstone in MG management, the evolving therapeutic landscape provides new opportunities to enhance patient outcomes and quality of life. Future research should focus on long-term comparative studies, patient adherence, and cost-effectiveness to optimize MG treatment strategies. Keywords: Myasthenia gravis, intravenous immunoglobulin, IVIg, plasma exchange, FcRn inhibitors, complement inhibitors, corticosteroid-sparing, immunomodulation